PENGEMBANGAN HUTAN RAKYAT BERBASIS TANAMAN KARET (Hevea brasilliensis) DI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Ardiansyah Ardiansyah; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The rubber plant is the second commodity after palm plants in the village of Sedinginan and Banjar XII, but there are problems with low productivity because a lot of rubber plant been old and damaged thereby inhibiting the development of community forest based on rubber plant. The sampling method using the simple random sample.The collection of data used were primary and secondary data. The results of the research aspects of socio-cultural and economic impact on farmers in developing community forestbased on rubber plant, assessed from the age of farmers belonging to a productive and has experience in planting and maintenance of rubber plant.The low productivity of rubber plant, makes the net income of farmer is not enough for every day. The farmer factor do not conduct replanting,because some of rubber crop still young and no farmer budget do not conduct replanting. Strategies SWOT Analysis can be taken is to use superior seeds qualified and revive the tradition of rubber plant. In order for the production of rubber plants is better role of the Department of Forestry and required Plantation.                     Keyword:The Development Of Community Forest, Crop Rubber and District of Tanah Putih